Perlindungan Hukum terhadap Pembeli Lelang Eksekusi PUPN dalam Hal Objek Lelang Tanah Kabur - Afifah Nur Azizah; I Gede Widhiana Suarda; Firman Floranta Adonara (Syntax Idea)
Banks are one of the most important financial institutions and have a large role in the economic life of society, considering that banks are one of the people's choices that can provide credit facilities. Problems in the field are increasingly complex with various sources of data used as a reference to find answers from the processes carried out by researchers so that this problem approach method is a sub-method to be able to solve a problem. The auction principles based on the auction regulations include the principle of publicity, the principle of competition, the principle of certainty, the principle of accountability, the principle of efficiency, the principle of balance and the principle of justice in the land auction object, even though there is a certificate of title. on valid Land and SKPT, one of the principles that has not been implemented except for the principle of certainty because it does not involve BPN in taking care of the existence of the object prior to auctioning to find out the location of the land. As a result, one of the principles has an impact on the implementation of the auction principle, namely the principle of accountability and the principle of justice, which is not realized